CROWDFUNDING SEBAGAI AKSES ALTERNATIF PERMODALAN BERBASIS TEKNOLOGI DIGITAL PADA KEGIATAN PERTANIAN (STUDI KASUS DI PT CROWDE MEMBANGUN BANGSA) - Astari Avisha; Anne Charina; Trisna Insan Noor; Gema Wibawa Mukti (Universitas Galuh Ciamis, 2019)
Currently the development of the financial services industry with a touch of technological innovation or called financial technology (Fintech) began to penetrate into the agricultural sector, even utilization is used to work on the scale of business at the farm level. One form of Fintech implementation in the agricultural sector is crowdfunding which is a fund raising activity for farmers capital by online using digital media (internet). One of the crowdfunding platforms in Indonesia which is engaged in agriculture is Crowde. This study aims to find out the description of crowdfunding management concepts conducted by Crowde as access to alternative capital based on digital technology on agricultural activities and to know the response of farmers partners to the concept of crowdfunding conducted by Crowde. The research technique used is case study with descriptive qualitative design using Milles Model and Huberman approach. The results show that during the planning phase, Crowde conducts farmer profilling and project analysis, and establishes provision fees. While the implementation stage of crowdfunding involves raising funds on the website, channeling capital through a farm shop and refunding investors through the Wallet feature. While the controlling phase takes place during the project through the project monitoring and reporting system. Crowde partner farmers showed a positive response to the crowdfunding scheme as access to capital. Most of the partner farmers say the process or procedure of the capital scheme is very easy to follow and judge that the crowdfunding model is very useful and suitable as access to farmers' capital.